Establishing a kinetic model of biomass-derived disaccharide hydrolysis over solid acid: A case study on hierarchically porous niobium phosphate - Liu, Qian; Liu, Haichao; Gao, Da-Ming (Chemical engineering journal (Lausanne, Switzerland : 1996), 2022)
[Display omitted] •Macroscopic kinetic models of disaccharides hydrolysis were established.•NbP showed high catalytic performance in hydrolysis of disacchrides.•The reaction order is 1.0 over all the substrates and 0.45–0.82 over the acid site.•Decomposition is more sensitive to temperature change than hydrolysis.•The consecutive reaction of monosaccharides occurred in bulk aqueous solution. Macroscopic kinetic models were established to describe the overall hydrolysis process of disaccharides with different type of glycosidic bond and constituted monosaccharides over hierarchically porous niobium phosphate (NbP) aiming for evaluating reaction efficiency of saccharide hydrolysis over solid acid. The NbP sample was synthesized by a sol–gel method accompanied by phase separation with co-continuous macroporous structure and high P/Nb molar ratio. The synthesized NbP sample showed high catalytic performance in the hydrolysis of disaccharides in an aqueous solution. Sucrose with α(1 → 2) glycosidic bond was the most easily hydrolyzed, with almost 100% conversion and monosaccharide yield, followed by melibiose α(1 → 6) and maltose α(1 → 4), while cellobiose β(1 → 4) was the strongest against to be hydrolyzed. The kinetic analysis showed that the reaction order is 1.0 over all the substrates and varied from 0.45 to 0.82 over the acid site, depending on the type of disaccharide. The activation of the decomposition reaction was larger than that of hydrolysis reaction, indicating that decomposition is more sensitive to temperature change than hydrolysis. Accordingly, direct decomposition of the disaccharides and the constituent monosaccharides synergistically determined the final yield and selectivity of the monosaccharides. Further, the decomposition and dehydration of glucose and galactose were found to occur in the bulk aqueous solution instead of on the surface of NbP.